Avoiding oversizing in sutureless valves leads to lower transvalvular gradients and less permanent pacemaker implants postoperatively. (11th June 2022) - Szecel, Delphine; Lamberigts, Marie; Rega, Filip; Verbrugghe, Peter; Dubois, Christophe; Meuris, Bart
Abstract: OBJECTIVES: The aim of this study was to evaluate the impact of changing the sizing strategy in aortic valve replacement using the Perceval sutureless prosthesis on haemodynamic outcomes and postoperative pacemaker implantation. METHODS: Retrospective analysis of patients implanted with the Perceval valve between 2007 and 2019 was performed by comparing patients implanted before the modification of sizing strategy (OLD group) and after (NEW group). The outcome parameters evaluated were the implanted prosthesis size, haemodynamical profile and postoperative pacemaker implantation. RESULTS: The entire patient cohort (784 patients) consisted of 52% female patients, with a mean age of 78.53 [standard deviation (SD): 5.8] years and a mean EuroSCORE II of 6.3 (range 0.7–76). In 55.5% of cases, surgery was combined. The NEW cohort had more male patients (54.6% vs 43.4%) ( P = 0.002). Mean implanted valve size, corrected for body surface area, was significantly lower in the NEW cohort (13.1, SD: 1.4 vs 13.5, SD: 1.4 mm/m 2, P < 0.001). The 30-day mortality was 3.4%. Peak and mean transvalvular gradients at discharge were significantly lower in the NEW versus OLD groups: 24.4 mmHg (SD: 9.2) versus 28.4 mmHg (SD: 10.3) ( P < 0.001) and 13.6 mmHg (SD: 5.3) versus 15.5 mmHg (SD: 6.0) ( P < 0.001). The mean effective opening area and the indexed effective opening area, respectively, increased from 1.5 cm 2 (SD: 0.5) and 0.85 cm 2 /m 2 (SD: 0.27) in the OLD group to 1.7 cm 2 (SD: 0.5) and 0.93 cm 2 /m 2 (SD: 0.30) in the NEW group ( P < 0.001). No difference was found in paravalvular leakage ≥1/4. Centrovalvular leakage ≥1/4 significantly decreased from 18% to 7.9% ( P < 0.001). With the new sizing, the new postoperative pacemaker implantation rate decreased significantly from 11% to 6.1% ( P = 0.016). CONCLUSIONS: Correct sizing of sutureless aortic valves is crucial to obtain the best possible haemodynamics and avoid complications. Abstract : A decade ago, aortic sutureless valves like Perceval (Corcym, Milan, Italy) were introduced into clinical practice.